2020
DOI: 10.1155/2020/3057168
|View full text |Cite
|
Sign up to set email alerts
|

Antithrombotic Treatments in Patients with Chronic Coronary Artery Disease or Peripheral Artery Disease: A Systematic Review of Randomised Controlled Trials

Abstract: Aims. Acetylsalicylic acid (ASA) is widely used for the prevention of atherothrombotic events in patients with chronic coronary artery disease (CAD) and peripheral artery disease (PAD), but the risk of vascular events remains high. We aimed at identifying randomised controlled trials (RCTs) on antithrombotic treatments in patients with chronic CAD or PAD. Methods. Searches were conducted on MEDLINE, EMBASE, and CENTRAL on March 1st, 2018. This systematic review (SR) uses a narrative synthesis to summarize the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 29 publications
1
9
0
Order By: Relevance
“…CHARISMA's [4] primary bleeding outcome was severe GUSTO bleeding (ICH or bleeding resulting in substantial hemodynamic compromise requiring treatment), while COMPASS utilized a modified ISTH major bleeding definition (fatal or symptomatic critical organ bleeding, bleeding into a surgical site requiring reoperation, or bleeding requiring hospitalization) [3]. Prior antithrombotic trial analyses have suggested the GUSTO severe and ISTH major bleeding definitions are not in close agreement regarding bleed severity, with only ~25% of ISTH major bleeds categorized as GUSTO severe [11,17]. To address this issue, we utilized supplemental data from both RCTs, enabling us to compare a combined moderate-to-severe GUSTO bleeding outcome from CHARISMA [18] to either an a priori modified ISTH bleeding [3] or an adjudicated, investigator severity-ranked moderate-to-severe bleeding definition for COMPASS [17].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…CHARISMA's [4] primary bleeding outcome was severe GUSTO bleeding (ICH or bleeding resulting in substantial hemodynamic compromise requiring treatment), while COMPASS utilized a modified ISTH major bleeding definition (fatal or symptomatic critical organ bleeding, bleeding into a surgical site requiring reoperation, or bleeding requiring hospitalization) [3]. Prior antithrombotic trial analyses have suggested the GUSTO severe and ISTH major bleeding definitions are not in close agreement regarding bleed severity, with only ~25% of ISTH major bleeds categorized as GUSTO severe [11,17]. To address this issue, we utilized supplemental data from both RCTs, enabling us to compare a combined moderate-to-severe GUSTO bleeding outcome from CHARISMA [18] to either an a priori modified ISTH bleeding [3] or an adjudicated, investigator severity-ranked moderate-to-severe bleeding definition for COMPASS [17].…”
Section: Discussionmentioning
confidence: 99%
“…Bauersachs et al [11] previously performed a systematic review addressing a similar (though somewhat broader) key question with their literature search extending through February 2018. We updated the Cochrane CENTRAL, MEDLINE and EMBASE searches (Table S1) of Bauersachs et al from March 1, 2018 through August 23, 2021.…”
Section: Information Sources and Search Strategymentioning
confidence: 99%
See 2 more Smart Citations
“…In the systematic review and meta-analysis on the use of rivaroxaban in coronary artery disease, it was concluded that patient's characteristics of ischemic and bleeding risk are critical in deciding about the addition of rivaroxaban [ 40 ]. The low-dose rivaroxaban in peripheral arterial disease was studied in the systematic review of randomized trials, and it was found to be effective in preventing cardiovascular events with a possible increase risk of bleeding [ 41 ].…”
Section: Role In Peripheral Artery Disease and Chronic Coronary Armentioning
confidence: 99%